IMPROVING MATHEMATICS LEARNING OUTCOMES OF THIRD GRADE STUDENTS ON THEME 6 THROUGH THE DEMONSTRATION METHOD - Erviatus Solichah; Agung Setyawan (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Mathematics is a subject that is often considered difficult by students. Therefore, there are many students who have low mathematics learning outcomes. Therefore, the purpose of this study was to determine the improvement of mathematics learning outcomes on the theme of 6 standard time unit materials through the demonstration method. This method is expected to be able to present abstract mathematical concepts to be easier for students to understand. This research is a classroom action research with data collection methods in the form of observation, interviews, tests, and documentation. The collected data were then analyzed with the stages of reduction, display data, and conclusion. The results of this study indicate an increase in mathematics learning outcomes for third grade students at SDN 2 Talunrejo. In cycle 1 the average student learning outcomes are 67 while in cycle 2 the average student learning outcomes are 79, then the average student learning outcomes increase by 12. While the percentage of student learning completeness in cycle 1 is 60% while in cycle 2 by 80%, then the percentage of student learning completeness increased by 20%. It can be concluded, based on these data, that the initial learning target of the demonstration method has been achieved, namely improving student learning outcomes in mathematics at SDN 2 Talunrejo.